Wykorzystanie rolnictwa do celów energetycznych w Polsce - Jasiulewicz, Michał (Utilization of Agriculture for Energetic Purposes in Poland, 2009)
In accordance with the EU directives, Poland is obliged to increase the share of renewable energy in power industry, including the use of biomass. There are premises according to which biomass will play the most important part in the renewable sources of energy. The possibility to use fallow lands and to establish perennial plantations of fast growing energy plants constitutes a vital element of biomass production for energy purposes. Nevertheless, it is essential that a system of the supply and demand for biomass is created on the local market. It is possible and very advantageous for the economy, and it can be done by setting up local heat and power generating plants, which will produce energy for the national grid. This energy will be obtained by the combustion or gasification of biomass. Warm water from the electric power production system should be used on the local level for heating buildings in the existing heat distribution network, and also other facilities, such as greenhouses, swimming pools or production plants.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 273-286